Interest Rates as an Intervening Variable Mediating the Effect of Banking Liquidity and Inflation on Economic Growth - KHALILA HUSNASARI; MUHAMMAD IQBAL; ERVINA ROSARINA HASIBUAN (Universitas Persada Indonesia YAI, 2025)
The objective of this study is to explain how independent variables such as bank liquidity and inflation as measured by, affect economic growth with interest rates as an intervening variable. Bank liquidity is projected using the cash ratio, inflation is determined based on information from Statistics Indonesia (BPS), interest rates are projected using the BI rate, and economic growth is projected using gross domestic product (GDP). The regression technique that used in this study is panel data regression, which is a combination of cross-sectional data and time series data. To test the hypothesis in this study, panel data regression was used with the selected regression model, namely the Random Effect Model (REM). Data processing and hypothesis testing were performed using Eviews13 software. The sample involved 12 companies with the largest assets in the banking sector. This study concluded that liquidity doesn’t affect interest rates, while inflation affects interest rates. Liquidity doesn’t affect economic growth, while inflation and interest rates affect economic growth. Liquidity and inflation simultaneously affect interest rates and can explain 27% of interest rates. Then, liquidity, inflation, and interest rates simultaneously affect economic growth and can explain 99% of economic growth. Then, liquidity and inflation affect economic growth through interest rates. Keywords: Inflation, Liquidity, Interest Rates, Economic Growth